The Possible beneficial effects of Antioxidant drugs (Vitamin C and E) and Allopurinol in the management of Pre-eclamptic patients treated with Methyldopa. - Ahmed, Ghassan S.; Al-Sabbagh, May S. (Journal of the Faculty of Medicine Baghdad, 2010)
Background: Pre-eclampsia is culmination of a multi-step process that related in part to elevated oxidative stress and associated with hyperurecimia.Patients and methods: Thirty normotensive and hundred pre-eclamptic pregnant women attending to Al-Basra hospital of pediatrics, obstetrics and gynecology were participated in this study. The patients were randomized into six groups. They were treated with methyldopa alone, methyldopa plus vitamin C, methyldopa plus vitamin E, methyldopa plus vitamin C and E, and methyldopa plus allopurinol. The oxidative stress (MDA), renal function parameters, systolic and diastolic blood pressure were evaluated before treatment and 14 day after initiation of therapy.Results: Using allopurinol, vitamin C, vitamin E, and a combination of vitamin C and E together with methyldopa in pre-eclampsia can produce a significant reduction in the level of oxidative stress, on the other hand, some of these supplemental antioxidants can produce a significant reduction in systolic and diastolic blood pressures, serum creatinine and proteinurea as well as serum uric acid concentration in different extent.Conclusion: Antioxidants and allopurinol when co-administrated with methyldopa, improves the maternal and biochemical indicators of pre-eclampsia and produce a better control of blood pressure.